China's mental health support in response to COVID-19: progression, challenges and reflection - Yumeng Ju; Yan Zhang; Xiaoping Wang; Weihui Li; Roger M. K. Ng; Lingjiang Li (BMC, 2020)
Abstract The continued spread of the coronavirus disease 2019 (COVID-19) has a serious impact on everyone across the globe, both physically and psychologically. In addition to proactive measures addressing physical survival needs and health protection, China has launched a mental health support system to cope with the widespread psychological stress during the pandemic and its aftermath. In this debate, the authors attempted to depict and reflect upon the overall framework of China's mental health support, with particular reference to the psychological intervention in response to COVID-19 over the last few months. Although a lot of effort has been made to meet the mental health needs, the accessibility, acceptability and effectiveness of the support system still have much room for improvement. Therefore, it is very important to re-think the predicament and challenge on ways of enhancing public mental health emergency responses in China. The concepts of universality, timeliness and scientific rigour were proposed as a possible reform in preparation for large-scale natural or man-made disasters in the coming future.